Identification of (Novel) Immune Targets with Potential Roles in the Progression of Pancreatic Ductal Adenocarcinoma (PDAC) - Nsingwane, Zanele (University of the Witwatersrand, Johannesburg, 2024)
Background: Pancreatic ductal adenocarcinoma (PDAC) is a lethal cancer with a growing incidence and mortality despite novel therapeutic strategies. Its aggressiveness and difficulty to treat suggest the need for a better understanding of associated molecular mechanisms which could be targeted for treatment. The complement signalling pathway may play diverse roles in PDAC by eliciting an immune response, inducing inflammatory responses, and may elevate pathways linked to chemoresistance. However, their role in the progression of PDAC is not fully understood. This study aimed to identify potential immune response-related targets in a group of patients. Methods: In this study, 30 tissue samples (tumours and corresponding normal tissues) were obtained from 15 PDAC patients, 34 plasma samples were obtained from 25 PDAC patients, 6 patients with chronic pancreatitis, and 3 healthy control participants. Targeted pathway-specific PCR analysis was conducted to determine the gene expression profiles of immune-response-related genes. The circulating levels of complement proteins C3 and C5 were further investigated. Pharmacological inhibition of the complement pathway in MIA PaCa-2 pancreatic cancer cell lines was performed and the effect on cells was assessed by cell proliferation, cell migration, and cell cycle assays. Finally, SWATH-mass spectrometry was performed to identify potential molecular mechanisms during inhibition. Results: The results identified C3 to be overly expressed in early PDAC compared to later stages in plasma (p=0.047). Pharmacological inhibition of the complement pathway led to increased cell growth (p<0.0001), proliferation (p=0.001) and migration (p=0.002) in vitro. Proteomic analysis implicated several proteins such as the mitochondrial and histone proteins, that could play a role in inducing this phenotype. Conclusion: Both Complement C3 and C5 are elevated in PDAC samples compared to healthy ones. Furthermore, the inhibition of the complement pathway was shown in vitro to result in a more aggressive phenotype by stimulating cellular growth, proliferation, and migration, indicating the involvement of complement C3 and C5 in tumour progression. This study helps to further delineate the role of the complement pathway in PDAC progression.
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy to the Department of Surgery, Faculty of Health Sciences, University of the Witwatersrand, , Johannesburg, 2024
Keywords: PDAC; Immune response; Cell migration; Complement pathway; Inflammation; UCTD; SDG-3: Good health and well-being